The Correlation of Antiretroviral Consumption Adherence on the Quality of Life of HIV Patients: A Systematic Review - Lailaturohmah Kurniawati; Nusalam Nursalam; Boby Sinuraya; Melya Nur Azizah (Indonesian Journal of Community Health Nursing, 2021)
Introduction: The use of antiretroviral therapy (ARV) occupies a major role in maintaining the immune system of patients with HIV / AIDS. Nowadays, there are still many cases of disobedient behavior in taking medication that affects the health condition and Quality of Life (QoL) of patients.This study aimed to conduct a systematic review of previous journals discussing the correlation of antiretroviral (ARV) consuming adherence to the Quality of Life (QoL) of HIV patients.Method: The literature searching process was specified on the five years latest research (2016-2020), selected from several indexed electronic databases (EBSCO, Science Direct, PubMed, Scopus, Proquest, Sage. Wiley, and DOAJ). Risk of Bias assessment tool using Joanna Briggs Institute (JBI) critical appraisal checklist, The research design selected was cross-sectional.Results: The search using a search engine resulted in a total of 723 articles and found 15 eligible journal manuscripts selected according to the criteria. The total number of respondents in this review were 5,416 respondents, with a total population involved between 83 and 1395 participants. There were 3 main discussions related to the adherence of antiretroviral (ARV) drugs consuming to the increased quality of life of HIV AIDS patients, factors that influenced adherence to Antiretroviral (ARV) therapy in HIV patients, and other supporting factors that affected the Quality of Life (QoL) other than ARV in HIV patients.Conclusion: There is correlation antiretroviral (ARV) drugs consuming adherence for QoL,there can improve the Quality of Life (QoL) of HIV patients.